Bran nue dae - Perkins, Rachel 1970-; Chi, Jimmy 1948-; Cribb, Reg; Lesnie, Andrew 1956-2015; Mailman, Deborah 1973-; Dingo, Ernie; Rush, Geoffrey 1951- (Reel DVD, 2011)
Willie lives in the sparkling beachside town of Broome in the late 1960s, his only care is getting the affections of local choir singer Rosie. His mother sends him away to further his education at Catholic Mission where young boys are forcefully encouraged to enter into priesthood by headmaster Father Benedictus. Willie escapes the mission and hitchhikes back to Broom with a new acquaintance Uncle Tadpole